2020
DOI: 10.1103/physrevlett.124.197801
|View full text |Cite
|
Sign up to set email alerts
|

Tale of Two Tails: Molecular Exchange Kinetics of Telechelic Polymer Micelles

Abstract: This thesis is submitted in partial fulfillment of the requirements for the degree of Philosophiae Doctor at the University of Oslo. It comprises five scientific articles, three of which have already been published in peer-reviewed journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 202 publications
(401 reference statements)
0
14
0
Order By: Relevance
“…In addition, the broad range of exchange rates might not only be caused by polydispersity of the chains. Computer simulations on amphiphilic block copolymer micelles have suggested that logarithmic relaxation can even occur for monodisperse chains, although in experiments with monodisperse core blocks, this logarithmic relaxation has not been observed. ,, The logarithmic relaxation in the computer simulations was explained by degeneracy of the energy states of the core blocks, which is broken when the chain leaves the core. If these degeneracy effects indeed could play a role in the exchange of amphiphilic diblock copolymer micelles, they might also play a role here.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the broad range of exchange rates might not only be caused by polydispersity of the chains. Computer simulations on amphiphilic block copolymer micelles have suggested that logarithmic relaxation can even occur for monodisperse chains, although in experiments with monodisperse core blocks, this logarithmic relaxation has not been observed. ,, The logarithmic relaxation in the computer simulations was explained by degeneracy of the energy states of the core blocks, which is broken when the chain leaves the core. If these degeneracy effects indeed could play a role in the exchange of amphiphilic diblock copolymer micelles, they might also play a role here.…”
Section: Resultsmentioning
confidence: 91%
“…(bottom) TR-SANS data of C 28 -PEO5/C 28 -PEO10-C 28 micelles obtained after mixing equal amounts of deuterated and protonated micelle solutions. Reproduced with permission from ref . Copyright 2020 American Physical Society.…”
Section: Deuteration and Neutron Scatteringmentioning
confidence: 99%
“…A structural study of telechelic poly(ethylene oxide) (PEO) chains in a dilute regime 6 has confirmed the formation of flower-like micelles for sufficiently high fraction of alkyl length of hydrophobic end blocks, leading to strong attraction of the hydrophobic groups and formation of clustered micelles with the presence of free dangling ends, when this attraction is reduced by reducing the alkyl length. In turn, a study 8 of the molecular exchange kinetics between micelles suggests a multi-step process of liberating the ends. However, topological transition between individual flower-like and star-like micelles in an extremely dilute regime is expected, 6 but has not been yet studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…pc(p, m) , (7) where c(m, p) is the number concentration of micelles composed of p tri-block copolymers and containing m free ends, V is the volume of the system. The last term fixes the total concentration of copolymers in the system c 0 , and the corresponding Lagrange multiplier µ 0 .…”
mentioning
confidence: 99%